Sztuka jako sposób włączania osób z niepełnosprawnością intelektualną do społeczeństwa - Pawlik, Sabina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Individuals with intellectual disabilities exist fully and authentically through works of art they have created. The universalism of the language of art happens to be for them a form of expression_ and, frequently, the only form of dialogue led with the outside world. Owing to art, an intellectually disabled person has a chance to go beyond the frames of his/her hermetic world. Art can be an import_ant stimulus influencing the social perception of individuals with intellectual disabilities. Furthermore, all the activities carried out in social, artistic and therapeutic fields can support the process of social inclusion of people with intellectual deficits.